Experiment-based Study on the Impact of Soiling on PV System’s Performance - Wan Juzaili Jamil; Hasimah Abdul Rahman; Kyairul Azmi Baharin (International Journal of Electrical and Computer Engineering (IJECE), 2016)
Soiling refers to the accumulation of dust on PV modules which plays a small but significant role in degrading solar photovoltaics system efficiency. Its effect cannot be generalized because the severity is location and environment dependent. Currently, there are limited studies available on the soiling effect in the hot and humid Malaysian tropical climate. This paper presents an experimental-based approach to investigate the effect of soiling on PV module performance in a tropical climate. The experiment involved a full day exposure of a polycrystalline PV module in the outdoors with accelerated artificial dust loading and an indoor experiment for testing variable dust dimensions. The findings show that for the worst case, the module’s output can be reduced by as much as 20%.